Nicolaus Goldmann (1611-1665) and the practice of the study (Bulletin KNOB, 1995)
In the middle of the seventeenth century Nicolaus Goldmann (1611-1665), who worked in Leyden as a private tutor of mathematics and architecture, published five books about architectural sciences. Two of these deal with fortification, one shows a mathematical design-instrument: the sector, another shows his own invention: an instrument for correctly designed columns.His fifth booklet gives a proposal for a true Vitruvian ionic scroll (part of the ionic capital). He designed a comprehensive measuring and design system for civil architecture. He worked in line with the scientific spirit of his time, proceeding from mathematics. He was part of the social environment of Leyden University and the University training of engineers.Apart from what Goldmann knew of German architecture and saw arising as Dutch Classicism, he absorbed the theoretical knowledge of his great predecessors from Italy. In the course of the lessons given by him in this field his insight matured. The lessons served as a basis for a theory which was definitely brought to completion in the form of a manuscript in 1659.The manuscript is probably the only complete theory of architecture ever written in the Dutch Republic. However, it was not published until the end of the seventeenth century, under a different title, under a different sky, and due to the engravings of a totally different character: in 1696 Goldmann's treatise was published in Wolfenbüttel as Vollstandige Anweisung zu der Civil-Baukunst, in an adaptation made by the mathematician and architect Leonhard Christoph Sturm (1669-1719).It is extraordinary that besides the printed publication the manuscript was also preserved in five copies. Apart from the book and the manuscripts, sketches, notebooks, calculations and a few printed works of Goldmann's hand have been preserved as well. With the aid of this material the printed book undergoes a remarkable transformation: from a late 17th-century publication in the dukedom of Braunschweig the range of thought returns to the atmosphere of Dutch Classicism of half a century earlier.This article gives a brief introduction to the life, writings and theory of architecture of Nicolaus Goldmann. The theory is sketched in broad lines on the basis of some examples from the manuscripts. Goldmann's drawings and comments are of great importance to understand the original text. They show us the principals of Goldmann's severe design-system and they create the building types which stay obscure in the later Sturm-edition.